Integrierte planare Antennen für supraleitende Detektorsysteme zur THz-Strahldiagnostik - Schmid, Alexander (Karlsruher Schriftenreihe zur Supraleitung, 2022)
In the THz frequency range, superconducting detectors coupled to planar antennas are well suited for the use in the field of accelerator beam diagnostics. This work studies the coupling efficiency and spectral sensitivity of different antenna designs. Based on the conclusions, two different detector systems for spectroscopic measurements are developed and verified with measurements at accelerator-based light sources.